EFFECT OF ECONOMIC STRESS ON ENTREPRENEURIAL INTENTION AMONG YOUTH IN ENUGU STATE, NIGERIA - Nebo, John C. (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2022)
Entrepreneurship is an essential pathway to addressing the impact of the declining economic realities of the present time. Although, there are indications that the intention to engage in entrepreneurial activities varies among individuals. Thus, this study aimed to investigate economic stress (ES) as a scarcely explored variable that could determine the variance in entrepreneurial intention (EI). Two hundred and eleven undergraduates were chosen at random from several institutes of higher learning in Enugu State. The Financial Stress Scale-College Version (FSS-CV) and the Entrepreneurial Intention Questionnaire were used to collect data for the study (EIQ). The results revealed a significant regression equation F (1,209), = 223.73, P<.05), with an R2 of 211 indicating that the ES contributed 21.1% of the variation in the youth's EI. Thus, the finding confirms the study's hypothesis that ES would significantly predict EI among the respondents. The practical implication and recommendations are discussed.